Regional trade is a reality - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The new ACP-EC Cotonou Agreement provides that in 2002 the EU and regional trade blocs in the ACP States (e.g. Caricom in the Caribbean, SADC in Southern Africa, SOPAC in the Pacific) will enter into negotiations on Regional Economic Partnership...